Difficulty Learning SKI for Students with Elementary School Background at MTs Negeri 2 Bengkulu City - Putri Julia; Inayah Latifah; Ismanur Hasanah; Anggun Tamara Tamesty; Jeni Efri Yani; Adicky Faturrahman; Hartoni Chandra (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to look at the conditions and situations in the learning process of Islamic Cultural History (SKI) at MTs Negeri 2 Bengkulu City. The research method used by researchers is a qualitative method which explains descriptively about SKI learning in this research using direct observation and interview methods by coming to the research location and directly to the r esearch subjects so that data collection can be carried out more effectively. Researchers found one problem at MTs Negeri 2 Bengkulu City, namely students' learning difficulties which affected students' interest, motivation and learning success. From this research, it was found that what causes learning difficulties for students at Mts Negeri 2 Bengkulu City is related to differences in students with elementary school and SD IT/MI educational backgrounds before entering MTs Negeri 2 Bengkulu City.